2018
DOI: 10.4103/ajm.ajm_200_17
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices associated with the diagnosis and management of skin and soft-tissue infections among medical students, residents, and attending physicians

Abstract: Skin and soft-tissue infections (SSTIs) are commonly encountered by medical students, residents, and trainees. The Infectious Diseases Society of America (IDSA) has updated its recommendations regarding SSTI diagnosis and management in June 2014. We assessed knowledge, attitude, and practices toward diagnosis and management of SSTIs using an online survey. We disseminated the survey to medical students, residents, and attending physicians practicing in family and internal medicine department at a university-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The oldest study was conducted in 2012 and the latest in 2020. We also included 10 multidisciplinary studies ( Table 2 ) that incorporated medical, pharmacy, dental, veterinary students, medical interns and physicians [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The oldest study was conducted in 2012 and the latest in 2020. We also included 10 multidisciplinary studies ( Table 2 ) that incorporated medical, pharmacy, dental, veterinary students, medical interns and physicians [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding implicates the importance of guidelines in undergraduate medical education in the early stage of the curricula. In any case, in all studies, medical students would appreciate more education in both basic science as well as clinical grounds so that they feel better prepared in their future tasks of everyday clinical practice [ 10 , 12 , 16 , 18 , 19 , 22 , 31 , 35 , 36 , 39 ]. It is of interest to note that, overall, following the WHO Global Action Plan on Antimicrobial Resistance [ 11 ], medical education about AMS might be essentially different in individual countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beatty et al showed 34.4% of the physicians and medical students were familiar with SSTI diagnosis and management as described in the IDSA guidelines. 8 Kessler et al found 15.7% of physicians aware of SSTI MRSA prevalence and 69.7% would use an antibiotic with MRSA coverage. 9 Szczypinska et al demonstrated antibiotic selection was based on strong physician preference of one antibiotic regimen over another.…”
Section: Discussionmentioning
confidence: 99%